2001
DOI: 10.1007/s11882-001-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Animal allergens and their control

Abstract: Animal allergens play a significant role in the pathogenesis of asthma and allergic rhinitis, and are potent causes of acute and chronic symptoms. Although cat and dog allergens are the most important, exposure to a wide variety of other furred animals is not uncommon. Recent reports state that 60% to 70% of households in the western world have at least one pet. Because of this significant exposure, hypersensitivity to animals has become increasingly important. This review focuses on the importance of animal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Clinical manifestations of the cat allergy include chronic allergic rhinitis (AR) and asthma which impair the patient’s capacity and increase economic burden. The cat allergens may be found in places without cats or they remain for many months after the cats were taken away and the places were regularly cleaned [ 3 , 4 ]. Therefore avoiding cats for morbidity intervention is a difficult practice for the cat allergic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of the cat allergy include chronic allergic rhinitis (AR) and asthma which impair the patient’s capacity and increase economic burden. The cat allergens may be found in places without cats or they remain for many months after the cats were taken away and the places were regularly cleaned [ 3 , 4 ]. Therefore avoiding cats for morbidity intervention is a difficult practice for the cat allergic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that 50-70% of the children with bronchial asthma have sensitivity to pets [34,36,37]. Such high rates are the results of the trend of feeding pets at home that leads to high level exposure sensitization [38]. Among pets, cat allergy is the most common type of animal allergy.…”
Section: Animalsmentioning
confidence: 99%
“…In the studies conducted on that issue, it has been reported that HEPA filters and vacuum cleaning lead to short term decrease in the cat/dog allergen levels, however, they do not change the levels of dust allergen concentrations [11,14,40]. Results of studies have suggested that the removal of pets from house has provided optimal pharmacotherapy reduced airway responsiveness significantly to methacholine, but no significant differences has occurred in the change of FEV1 [37,38,41]. Furthermore, it has also been stated in this study that the removal of pets from the house has led to a reduce in the doses of inhaled corticosteroids and in the frequency of follow-up visits.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations